ANALISIS FAKTOR PENDUKUNG DAN PENGHAMBAT IMPLEMENTASI PROGRAM BANK SAMPAH DALAM MENINGKATKAN ECOLOGICAL CITIZENSHIP MASYARAKAT DESA PATARUMAN KABUPATEN BANDUNG BARAT - Rafli Saputro, Faizal; Syaifullah; Setiawan, Mursyid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the supporting and inhibiting factors in the implementation of the waste bank program to improve ecological citizenship in the community of Pataruman Village, West Bandung Regency. This study uses a qualitative approach with a case study method that explains the real situation on the ground. The focus of this research is directed at the extent to which the waste bank program is optimal in improving ecological citizenship in Pataruman Village. However, implementation in the field still faces obstacles, such as a lack of facilities and infrastructure, limited funding, and limited human resources. It can be concluded that the implementation of the waste bank is progressing well, with gradual changes in the community's attitude toward waste as having economic value. This requires consistent government support regarding the sustainable waste bank program.